Exploring hedonic and status appeals of vacation among Malaysian female travelers and implication on marketing - Teo, Carol Boon Chui; Md. Sidin, Samsinar (World Cultural Tourism Association, 2010)
The region-wide market trend shows the emergence of a female market for outbound travel. Personal travel forms a component of hybrid lifestyles of women today. More Malaysian women travel attributed to mindset shifts from traditional role to modem role, aided by entry of low cost carriers and online ticketing. This paper investigates hedonic and status appeals of vacation and the mediating effect of individual hedonic orientation on status consumption. The study utilized triangulation approach. Focus group discussions identified hedonistic and status appeals of female vacation consumption. Survey indicated hedonic experiences in vacation had indirect impact on status consumption through individual hedonic orientation. The hedonistic and status-seeking behavior in women's travel lifestyle has widespread marketing implications in the female travelers market.